THE IMPACT OF ONLINE ENVIRONMENT ON TOURISM - SOFRONOV, Bogdan (Annals of Spiru Haret University. Economic Series, 2018)
The online tourism is part of e-commerce and unites some of the fastest growing technologies, such as communications and information technology, the hospitality industry, and strategic management / marketing / planning. Online tourism activities involve tour operators, travel agencies and other entities with tourism-related interests in the virtual space through a dedicated portal. The phenomenon itself has implications for the tourist services consumer. The internet has revolutionized the travel industry both as a source of information and like a sales channel. Online marketing, photographs, and consumer reviews are bringing destinations and attractions to the screens of potential travelers around the world. The ease with which a customer can review and compare travel options opens up new markets for both large and small businesses and the ability to confirm prices and purchase services online benefits travelers and businesses alike.